2016
DOI: 10.1002/humu.23045
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Genetic Variation: From Population Analysis to Functional Implications of Three Allele Variants Associated with Cancer

Abstract: Nucleotide variants in microRNA regions have been associated with disease; nevertheless, few studies still have addressed the allele-dependent effect of these changes. We studied microRNA genetic variation in human populations and found that while low-frequency variants accumulate indistinctly in microRNA regions, the mature and seed regions tend to be depleted of high-frequency variants, probably as a result of purifying selection. Comparison of pairwise population fixation indexes among regions showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 70 publications
6
20
0
Order By: Relevance
“…We found that most of the SNPs (1833 SNPs, 97.5%, Table S1 ) in miRNA seed regions were rare variants (defined as SNPs with minor allele frequency (MAF) < 5%). Recently, Torruella-Loran et al [ 18 ] studied miRNA genetic variation in human populations and found that the seed regions tend to be depleted of high-frequency variants, which is consistent with our finding. We also found that there are 1587, 749, 340, 102, 31, and 4 miRNAs, which carry zero, one, two, three, four, and five SNPs, respectively, in their seed region (Figure S1 , Table S1 ).…”
Section: Resultssupporting
confidence: 92%
“…We found that most of the SNPs (1833 SNPs, 97.5%, Table S1 ) in miRNA seed regions were rare variants (defined as SNPs with minor allele frequency (MAF) < 5%). Recently, Torruella-Loran et al [ 18 ] studied miRNA genetic variation in human populations and found that the seed regions tend to be depleted of high-frequency variants, which is consistent with our finding. We also found that there are 1587, 749, 340, 102, 31, and 4 miRNAs, which carry zero, one, two, three, four, and five SNPs, respectively, in their seed region (Figure S1 , Table S1 ).…”
Section: Resultssupporting
confidence: 92%
“…Our result was consistent with the Thakur et al results [42]. In 2016, Torruella-Loran et al found that rs11614913 in miR-196a2 has a function in regulating the expression of several genes involved in cancer [43]. SNPs located in the mature sequences of miRNA genes might affect miRNA biogenesis and recognition of target mRNAs [16].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, it has been demonstrated previously that the variant GG genotype of the polymorphism had the lowest delta CT value (which implied a high expression level), followed by AG and AA genotypes, although it was not clear whether the difference was statistically significant 26 . It has also been reported in an in vitro study that miR-499a originating from the two alleles of rs3746444 polymorphism reduced the expression of tumor suppressor genes to different extents 35 . Considering these previous findings, we postulate that the variant allele of the polymorphism gave rise to a higher level of miR-499a and caused a significant decrease in the expression of tumor suppressor genes, thereby leading to an increase in breast cancer susceptibility.…”
Section: Discussionmentioning
confidence: 85%